THE VISION OF THE EDUCATIONAL PROCESS IN POLISH AND UKRAINIAN CORE CIRRICULA. ANALYSIS BASED ON THE HOFSTEDE 4-D MODEL - POPYK, ANZHELA; ANNA PERKOWSKA-KLEJMAN, ANNA (Society Register, 2019)
National curricula are documents describing the knowledge, skills and social competences that students should acquire at the appropriate stages of education. In our article, we assume that these documents have the power to buttress the existing status quo or to change reality. Generally speaking, they are an attempt at transforming selected areas of culture in a deliberate, planned, and systemic manner. This paper, by means of Hofstede’s 4-D model of cultural differences among societies (viz power distance, uncertainty avoidance, individualism versus collectivism, masculinity versus femininity), is aimed at studying the way Polish and Ukrainian national curricula define the educational processes and Teacher-Student relations, in order to reveal the correlation between the cultural differences and learning/teaching process in Poland and Ukraine. A critical discourse analysis of the two state curricula has been done to interpret their contents.